Dextran-Coated Magnetic Supports Modified with a Biomimetic Ligand for IgG Purification - Santana, Sara D. F. (2012)
The authors thank the financial support from Fundacao para a Ciencia e a Tecnologia through Grant PEst-C/EQB/LA0006/2011 and contracts no. PTDC/EBB-BIO/102163/2008, PTDC/EBB-BIO/098961/2008, PTDC/EBB-BIO/118317/2010, SFRH/BD/72650/2010 for V.L.D, and Santander Totta Bank - Universidade Nova de Lisboa for the Scientific Award 2009/2010. The authors are grateful to Dr. Abid Hussain and M. Telma Barroso (REQUIMTE, FCT-UNL, Portugal) for the preparation of the synthetic affinity ligands, to Lonza Biologics, U.K. (Dr. Richard Alldread), and the Animal Cell Technology Unit of ITQB-UNL/IBET (Dr. Paula M Alves and Dr. Ana Teixeira) for providing the cells and the culture bulks and to Mr. Filipe Cardoso and Prof. Paulo Freitas (INESC-MN, Lisbon, Portugal) for the help with the VSM measurements.